27.3k views
4 votes
For f(x)=4x+1 and g(x)=x^2-5, find (f-g)(x).

For f(x)=4x+1 and g(x)=x^2-5, find (f-g)(x).-example-1
User Smchae
by
5.1k points

2 Answers

5 votes

Answer:

C

Explanation:

note (f - g)(x) = f(x) - g(x)

f(x) - g(x)

= 4x + 1 - (x² - 5) ← distribute by - 1

= 4x + 1 - x² + 5 ← collect like terms

= - x² + 4x + 6 ← in standard form → C

User Fernando Tiberti
by
5.2k points
4 votes

For this case we have the following functions:


f (x) = 4x + 1\\g (x) = x ^ 2-5

We must find
(f-g) (x). By definition we have to:


(f-g) (x) = f (x) -g (x)

So:


(f-g) (x) = 4x + 1- (x ^ 2-5)

We take into account that:


- * + = -\\- * - = +\\(f-g) (x) = 4x + 1-x ^ 2 + 5\\(f-g) (x) = - x ^ 2 + 4x + 6

Answer:


(f-g) (x) = - x ^ 2 + 4x + 6

Option C

User Akousmata
by
5.6k points